Hot deformation behavior of micro-alloyed steel using processing maps developed with different constitutive equations - Thakur S.K.; Das A.K.; Jha B.K. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The hot workability of microalloyed steel was studied in the deformation temperature range of 850–1200ºC and strain rate of 0.001-100s-1. The constitutive relation of flow stress with temperature, strain rate and strain was established to construct processing maps of the microalloyed steel. The processing maps were constructed using conventional power law, integral method, and Arrhenius equations. The developed processing maps were used to predict the optimal hot deformation conditions and were validated with metallurgical examinations. The safe regime for hot working of the experimental steel was found to be in the intermediate temperature-strain rate range (1000-1150ºC;0.001-10 s-1), where the deformation process was dominated by dynamic recrystallization and dynamic recovery of the austenitic phase. The processing map constructed using Arrhenius equations increased continuously with an increase in deformation temperature and decrease in strain rate and it did not reveal relevant information of hot workability with respect to deformation temperature and strain rate. The dynamic recrystallization behavior of experimental steel was affected by both deformation temperature and strain rate which was explained in detail through microstructural examination.